Manganese zinc ferrite material as well as preparation method and application thereof
By adding Co2O3 to the manganese zinc ferrite material and optimizing the sintering process, the problem of unstable magnetic properties of manganese zinc ferrite material after high temperature aging is solved, and its anti-aging and service life are significantly improved.
Patent Information
- Application Number
- CN202310837819.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-10
- Publication Date
- 2025-01-10
AI Technical Summary
The existing manganese-zeb ferrite materials have unstable magnetic properties after high temperature aging, resulting in a shortened application life, and the existing technology has failed to effectively detect or solve this problem.
By adding Co2O3 as an additive to the manganese-zeb ferrite material, its content is controlled, the magnetostrictive coefficient and hysteresis loss is reduced, and a suitable sintering process is adopted to improve the aging resistance of the material.
The aging resistance of manganese-zeb ferrite materials is significantly improved, and the permeability change after oven baking is less than 14%, extending the service life of the material.
Smart Images

Figure BDA0004329490200000131
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of soft ferrites and relates to a manganese-zinc ferrite material and a preparation method and application thereof. Background Art
[0002] With the development of 5G communication technology and the widespread commercial use of third-generation semiconductors, power electronic components are accelerating towards high frequency, miniaturization and high energy efficiency. As the basic material of the contemporary electronic industry and information industry and the core material of power electronic components, manganese zinc ferrite materials have become the focus of research on high-frequency soft magnetic materials.
[0003] CN 115650718 A discloses a manganese-zinc ferrite material with ultra-wide temperature range, low power consumption and temperature stability of magnetic permeability and a preparation method thereof, wherein the main components include 53.00% to 53.30% of ferric oxide, 6.0% to 10.0% of zinc oxide, and the rest is manganese oxide. Within the ultra-wide temperature range of 0°C to 150°C, the power consumption of the material changes very little with temperature, within ±10%, the temperature power consumption curve basically presents a horizontal trend, and the magnetic permeability has good temperature stability, within ±15%, but the invention does not provide a description of the detection of the magnetic permeability after high-temperature aging.
[0004] CN 110183221 A discloses a method for preparing a manganese-zinc soft ferrite material with ultra-low temperature magnetic permeability stability, wherein the main components are Fe2O3, MnO and ZnO, and the corresponding molar ratio is (52.5-55.0):(34.0-36.5):(11.5-13.5). Compared with ordinary soft ferrite materials, the magnetic permeability of the soft ferrite material of the invention is significantly improved at low temperatures (-55°C to 25°C), but the magnetic permeability of the high temperature part (100°C to 140°C) is relatively low.
[0005] The manganese-zinc ferrite materials provided in the above technical solutions all have the characteristic of good magnetic permeability stability, but none of them discloses the change in magnetic permeability after aging the manganese-zinc ferrite material (placing it in an oven at a certain temperature and for a certain time), but its change will affect the application of the high-frequency manganese-zinc ferrite material.
[0006] Although manganese-zinc ferrite materials are sintered at high temperatures, their magnetic properties are still unstable in some situations. For example, when environmental factors such as time, temperature, frequency, magnetic field, stress, etc. change, the magnetic properties of manganese-zinc ferrite materials will also change. These instabilities often cause many application problems and bring a lot of trouble to users.
[0007] After the manganese-zinc ferrite magnetic components are manufactured and left naturally for a period of time, their magnetic properties will decline to varying degrees, and this decline is irreversible. Almost all manganese-zinc ferrites have this natural aging phenomenon. The aging problem of manganese-zinc ferrites will affect their service life and application, so special attention must be paid. In order to save time, the method of artificial accelerated aging is generally used, that is, the ferrite magnetic components are placed in an oven and heated for a certain period of time before use, and the changes in their magnetic permeability before and after aging are compared.
[0008] Therefore, it is urgent to develop a high-frequency manganese-zinc ferrite material with aging resistance and low loss. Summary of the invention
[0009] In order to solve the above technical problems, the present invention provides a manganese-zinc ferrite material and a preparation method and application thereof. The magnetostriction coefficient of the material itself is reduced by a suitable main formula, manganese-zinc ferrite containing Co ions is added and its content is controlled, the hysteresis loss is reduced, and the aging resistance of the material is improved.
[0010] To achieve this object, the present invention adopts the following technical solutions:
[0011] In a first aspect, the present invention provides a manganese-zinc ferrite material, the manganese-zinc ferrite material comprising a main component and an additive, the main component comprising Fe2O3, ZnO and MnO;
[0012] The additive includes Co2O3, and the mass of the Co2O3 is 800 to 2000 ppm of the total mass of the main component, for example, it can be 800 ppm, 1000 ppm, 1500 ppm or 2000 ppm, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0013] The invention reduces the magnetostriction coefficient of the material itself through a suitable main formula, adds manganese-zinc ferrite containing Co ions and controls the content thereof, reduces the hysteresis loss and improves the aging resistance of the material.
[0014] This is because after a long period of high temperature, the Co ions change from a metastable state to a stable state at a low energy level, resulting in a significant change in magnetic permeability. However, cobalt has a positive K1 (magnetocrystalline anisotropy constant) that compensates for the negative K1 value of manganese-zinc ferrite, which can reduce hysteresis loss and improve the temperature performance of the material.
[0015] Preferably, the main components include, by percentage of the total amount of the substance:
[0016] Fe2O3 52~56mol%
[0017] ZnO 4~7mol%
[0018] MnO balance.
[0019] 52-56 mol% Fe2O3, for example, can be 52 mol%, 53 mol%, 54 mol%, 55 mol% or 56 mol%, but is not limited to the listed values, and other values not listed within the numerical range are equally applicable; 4-7 mol% ZnO, for example, can be 4 mol%, 4.5 mol%, 5 mol%, 5.5 mol%, 6 mol%, 6.5 mol% or 7 mol%, but is not limited to the listed values, and other values not listed within the numerical range are equally applicable.
[0020] Preferably, the additive also includes any one of CaCO3, Nb2O5, ZrO2, V2O5 or TiO2, or a combination of at least two of them. Typical but non-limiting combinations include a combination of CaCO3 and Nb2O5, a combination of Nb2O5 and ZrO2, a combination of ZrO2 and V2O5, a combination of V2O5 or TiO2, a combination of CaCO3, Nb2O5 and ZrO2, a combination of Nb2O5, ZrO2, V2O5, or a combination of ZrO2, V2O5 or TiO2.
[0021] The present invention reduces material loss and improves material anti-aging properties through appropriate additive combination and addition amount. After the manganese-zinc ferrite material is placed in an oven and baked at 125°C and 150°C for 1000 hours, its magnetic permeability changes are less than 8% and 14% respectively.
[0022] Preferably, the mass of the CaCO3 is 500 to 1000 ppm of the total mass of the main component, for example, it can be 500 ppm, 600 ppm, 700 ppm, 800 ppm, 900 ppm or 1000 ppm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0023] Preferably, the mass of the Nb2O5 is 200 to 500 ppm of the total mass of the main components, for example, it can be 200 ppm, 300 ppm, 400 ppm or 500 ppm, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0024] Preferably, the mass of ZrO2 is 100 to 300 ppm of the total mass of the main components, for example, it can be 100 ppm, 150 ppm, 200 ppm, 250 ppm or 300 ppm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0025] Preferably, the mass of the V2O5 is 100 to 300 ppm of the total mass of the main components, for example, it can be 100 ppm, 150 ppm, 200 ppm, 250 ppm or 300 ppm, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0026] Preferably, the mass of the TiO2 is 1500 to 3500 ppm of the total mass of the main components, for example, it can be 1500 ppm, 2000 ppm, 2500 ppm, 3000 ppm or 3500 ppm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0027] In a second aspect, the present invention provides a method for preparing the manganese-zinc ferrite material according to the first aspect, the preparation method comprising the following steps:
[0028] (1) mixing the main components according to the formula, performing a sand grinding and then pre-burning to obtain a pre-burned material;
[0029] (2) Mixing the additives and the obtained pre-sintered material, performing secondary sand grinding and then sintering to obtain the manganese-zinc ferrite material.
[0030] In the preparation process of the present invention, the main components are first mixed to make them uniform, and then a pre-sintering process is performed to grow a spinel structure, and then appropriate additives are added to the pre-sintered product, and secondary sand grinding is performed to make the powder reach a suitable particle size range. The present invention cannot mix the main components and additives at one time to prevent the grains from growing too large and being difficult to grind after the main components and additives are pre-sintered; furthermore, mixing at one time will cause the problem of inaccurate content of the additives. The method of the present invention can make the content of each component of the additive accurate.
[0031] Preferably, the one-time sanding process in step (1) also includes mixing water.
[0032] Preferably, the mass ratio of the main component to water is 1:(1.2-2.5), for example, it can be 1:1.2, 1:1.4, 1:1.6, 1:1.8, 1:2, 1:2.2 or 1:2.5, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0033] Preferably, the time for the first sanding in step (1) is 1 to 3 hours, for example, 1 hour, 1.4 hours, 1.8 hours, 2.2 hours, 2.6 hours or 3 hours, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0034] Preferably, the pre-burning temperature in step (1) is 750-850°C, for example, it can be 750°C, 760°C, 770°C, 780°C, 790°C, 800°C, 810°C, 820°C, 830°C, 840°C or 850°C, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0035] The pre-sintering temperature of the present invention needs to be in the range of 750-850°C. If the pre-sintering temperature is too high, the grains will grow too large and it will be difficult to grind them into a suitable particle size range within a specific time; if the pre-sintering temperature is too low, the powder activity will be too high, and the uniformity of the grain size after sintering will be poor, resulting in a product with more pores and poor performance.
[0036] Preferably, the pre-burning time in step (1) is 1 to 3 hours, for example, 1 hour, 1.4 hours, 1.8 hours, 2.2 hours, 2.6 hours or 3 hours, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0037] Preferably, the pre-firing atmosphere in step (1) is an air atmosphere.
[0038] Preferably, the time for the secondary sanding in step (2) is 2 to 4 hours, for example, 2 hours, 2.4 hours, 2.8 hours, 3.2 hours, 3.6 hours or 4 hours, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0039] Preferably, the median particle size of the powder obtained after the secondary sand grinding in step (2) is 0.8 to 1.2 μm, for example, it can be 0.8 μm, 0.9 μm, 1 μm, 1.1 μm or 1.2 μm, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0040] Preferably, the secondary sand grinding in step (2) further includes screening, granulation and molding.
[0041] Preferably, the mesh size of the sieving is 30 to 80 meshes, for example, 30 meshes, 40 meshes, 50 meshes, 60 meshes, 70 meshes or 80 meshes, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0042] Preferably, a granulating agent is added during the granulation process.
[0043] Preferably, the granulating agent comprises PVA and / or PVB.
[0044] Preferably, the mass of the granulating agent is 8 to 15 wt% of the mass of the powder after secondary sand grinding, for example, it can be 8 wt%, 9 wt%, 10 wt%, 11 wt%, 12 wt%, 13 wt%, 14 wt% or 15 wt%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0045] Preferably, the sintering in step (2) is carried out under a balanced oxygen partial pressure atmosphere.
[0046] Preferably, the sintering in step (2) includes a first sintering, a second sintering, a third sintering and a fourth sintering.
[0047] The sintering process of the present invention adopts a four-stage heat preservation sintering process. In the first sintering, some of the more active granular powders react first, and the grains partially grow. In the second sintering, the temperature continues to increase, and the less active granular powders also begin to react, and the overtemperature sintering can promote grain growth and increase the sintering density. The first and second sinterings work together to make the grain size larger and more uniform. In the third sintering, the appropriate oxygen content and temperature ensure the loss of the sample ring and other properties. The fourth sintering and the termination temperature after the fourth sintering can remove the stress generated when the divalent iron and the trivalent iron are converted to each other, thereby ensuring the performance.
[0048] Preferably, the first sintering temperature is 1000-1100°C, for example, 1000°C, 1020°C, 1040°C, 1060°C, 1080°C or 1100°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0049] Preferably, the holding time of the first sintering is 0.5 to 1 h, for example, 0.5 h, 0.6 h, 0.7 h, 0.8 h, 0.9 h or 1 h, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0050] Preferably, the heating rate of the first sintering is 1-3°C / min, for example, 1°C / min, 1.5°C / min, 2°C / min, 2.5°C / min or 3°C / min, but is not limited to the listed values, and other values not listed in the numerical range are also applicable. The heating rate of the first sintering refers to the heating rate of the process of heating from a certain initial temperature that is not specifically limited to the temperature of the first sintering.
[0051] Preferably, the second sintering temperature is 1100-1200°C, for example, 1100°C, 1120°C, 1140°C, 1160°C, 1180°C or 1200°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0052] Preferably, the holding time of the second sintering is 0.1-0.5 h, for example, 0.1 h, 0.2 h, 0.3 h, 0.4 h or 0.5 h, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0053] Preferably, the heating rate of the second sintering is 3-5°C / min, for example, 3°C / min, 3.5°C / min, 4°C / min, 4.5°C / min or 5°C / min, but is not limited to the listed values, and other values not listed in the numerical range are also applicable. The heating rate of the second sintering refers to the heating rate of the process from the temperature of the first sintering to the temperature of the second sintering.
[0054] Preferably, the temperature of the third sintering is 1000-1100°C, for example, it can be 1000°C, 1020°C, 1040°C, 1060°C, 1080°C or 1100°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0055] Preferably, the holding time of the third sintering is 3 to 5 hours, for example, 3 hours, 3.5 hours, 4 hours, 4.5 hours or 5 hours, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0056] Preferably, the cooling rate of the third sintering is 3-5°C / min, for example, 3°C / min, 3.5°C / min, 4°C / min, 4.5°C / min or 5°C / min, but is not limited to the listed values, and other values not listed in the numerical range are also applicable. The cooling rate of the third sintering refers to the cooling rate of the process from the temperature of the second sintering to the temperature of the third sintering.
[0057] Preferably, the fourth sintering temperature is 250-300°C, for example, 250°C, 260°C, 270°C, 280°C, 290°C or 300°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0058] Preferably, the fourth sintering holding time is 3 to 5 hours, for example, 3 hours, 3.5 hours, 4 hours, 4.5 hours or 5 hours, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0059] Preferably, the cooling rate of the fourth sintering is 2.5-5°C / min, for example, 2.5°C / min, 3°C / min, 3.5°C / min, 4°C / min, 4.5°C / min or 5°C / min, but is not limited to the listed values, and other values not listed in the numerical range are also applicable. The cooling rate of the fourth sintering refers to the cooling rate of the process from the temperature of the third sintering to the temperature of the fourth sintering.
[0060] Preferably, after the fourth sintering is completed, the temperature is lowered to the termination temperature.
[0061] Preferably, the termination temperature is 40-80°C, for example, 40°C, 50°C, 60°C, 70°C or 80°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable; preferably, it is 50-70°C.
[0062] Preferably, the cooling rate to the termination temperature is 0.1-0.5°C / min, for example, 0.1°C / min, 0.2°C / min, 0.3°C / min, 0.4°C / min or 0.5°C / min, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0063] As a preferred technical solution of the preparation method described in the second aspect of the present invention, the preparation method comprises:
[0064] (1) mixing the main components according to the formula amount, mixing the main components with water at a mass ratio of 1: (1.2-2.5), sand-milling for 1-3 hours, drying, and then pre-calcining at a temperature of 750-850° C. for 1-3 hours in an air atmosphere to obtain a pre-calcined material;
[0065] (2) mixing the additive and the obtained pre-sintered material, performing secondary sand milling for 2 to 4 hours, drying to obtain a sand milled powder with a median particle size of 0.8 to 1.2 μm, passing the sand milled powder through a 30 to 80 mesh sieve, granulating, molding and sintering to obtain the manganese zinc ferrite material;
[0066] The sintering process includes: in a balanced oxygen partial pressure atmosphere, heating to 1000-1100°C at a rate of 1-3°C / min for a first sintering for 0.5-1h, then heating to 1100-1200°C at a rate of 3-5°C / min for a second sintering for 0.1-0.5h, then cooling to 1000-1100°C at a rate of 3-5°C / min for a third sintering for 3-5h, then cooling to 250-300°C at a rate of 2.5-5°C / min for a fourth sintering for 3-5h, and finally cooling to a termination temperature of 40-80°C at a rate of 0.1-0.5°C / min.
[0067] In a third aspect, the present invention provides an application of the manganese-zinc ferrite material according to the first aspect, wherein the manganese-zinc ferrite material is used for power electronic components.
[0068] Compared with the prior art, the present invention has at least the following beneficial effects:
[0069] The invention reduces the magnetostriction coefficient of the material itself through a suitable main formula, adds manganese-zinc ferrite containing Co ions and controls the content thereof, reduces the hysteresis loss and improves the aging resistance of the material. DETAILED DESCRIPTION
[0070] For the convenience of understanding the present invention, the present invention lists the following embodiments. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0071] Example 1
[0072] The present embodiment provides a manganese-zinc ferrite material, which consists of a main component and additives. The main component is: 54.2 mol% Fe2O3, 5.2 mol% ZnO and the remainder MnO, and the additives are: 1500 ppm Co2O3, 800 ppm CaCO3, 300 ppm Nb2O5, 200 ppm ZrO2, 250 ppm V2O5 and 2000 ppm TiO2 based on the total mass of the main components.
[0073] The preparation method of the manganese-zinc ferrite material comprises:
[0074] (1) mixing a main component of 54.2 mol% Fe2O3, 5.2 mol% ZnO and the balance MnO, mixing the main component with water at a mass ratio of 1:1.5, sand-milling for 1 hour and drying, and then pre-calcining at 800°C for 3 hours in an air atmosphere to obtain a pre-calcined material;
[0075] (2) mixing the additive and the obtained pre-sintered material, performing secondary sand grinding for 2 hours, drying to obtain a sand-ground powder with a median particle size of 1 μm, passing the sand-ground powder through a 60-mesh sieve, granulating, and molding to obtain a standard sample ring blank with a size of 12.5 mm×7.5 mm×7 mm, and then sintering to obtain the manganese-zinc ferrite material;
[0076] The additives include, by total mass of main components: 1500 ppm Co2O3, 800 ppm CaCO3, 300 ppm Nb2O5, 200 ppm ZrO2, 250 ppm V2O5 and 2000 ppm TiO2;
[0077] The sintering process includes: in a balanced oxygen partial pressure atmosphere, heating to 1080°C at a rate of 1.5°C / min for a first sintering for 1 hour, then heating to 1160°C at a rate of 3.5°C / min for a second sintering for 0.5 hour, then cooling to 1100°C at a rate of 3.5°C / min for a third sintering for 5 hours, then cooling to 300°C at a rate of 2.5°C / min for a fourth sintering for 3 hours, and finally cooling to a termination temperature of 50°C at a rate of 0.1°C / min.
[0078] Example 2
[0079] The present embodiment provides a manganese-zinc ferrite material, which consists of a main component and additives. The main component is: 52 mol% Fe2O3, 7 mol% ZnO and the remainder MnO, and the additives are: 800 ppm Co2O3, 500 ppm CaCO3, 500 ppm Nb2O5, 300 ppm ZrO2, 300 ppm V2O5 and 1500 ppm TiO2 based on the total mass of the main components.
[0080] The preparation method of the manganese-zinc ferrite material comprises:
[0081] (1) mixing a main component of 52 mol% Fe2O3, 7 mol% ZnO and the balance MnO, mixing the main component with water at a mass ratio of 1:1.2, sand-milling for 3 hours and drying, and then pre-calcining at 750°C for 3 hours in an air atmosphere to obtain a pre-calcined material;
[0082] (2) mixing the additives and the obtained pre-sintered material, performing secondary sand grinding for 4 hours, drying to obtain a sand-ground powder with a median particle size of 0.8 μm, passing the sand-ground powder through a 30-mesh sieve, granulating, and molding to obtain a standard sample ring blank with a size of 12.5 mm×7.5 mm×7 mm, and then sintering to obtain the manganese-zinc ferrite material;
[0083] The additive comprises, by total mass of main components, 800 ppm of Co2O3, 500 ppm of CaCO3, 500 ppm of Nb2O5, 300 ppm of ZrO2, 300 ppm of V2O5 and 1500 ppm of TiO2;
[0084] The sintering process includes: in a balanced oxygen partial pressure atmosphere, heating to 1000°C at a rate of 1.5°C / min for a first sintering for 1 hour, then heating to 1100°C at a rate of 3°C / min for a second sintering for 0.5 hour, then cooling to 1000°C at a rate of 3.5°C / min for a third sintering for 5 hours, then cooling to 300°C at a rate of 2.5°C / min for a fourth sintering for 3 hours, and finally cooling to a termination temperature of 40°C at a rate of 0.1°C / min.
[0085] Example 3
[0086] The present embodiment provides a manganese-zinc ferrite material, which consists of a main component and additives, the main component being 56 mol% of Fe2O3, 4 mol% of ZnO and the remainder being MnO, and the additives being 800 ppm of Co2O3, 500 ppm of CaCO3, 500 ppm of Nb2O5, 300 ppm of ZrO2, 300 ppm of V2O5 and 1500 ppm of TiO2 based on the total mass of the main components.
[0087] The preparation method of the manganese-zinc ferrite material comprises:
[0088] (1) mixing a main component of 56 mol% Fe2O3, 4 mol% ZnO and the balance MnO, mixing the main component with water at a mass ratio of 1:2.5, sand-milling the mixture for 3 hours and drying the mixture, and then pre-calcining the mixture at a temperature of 850°C for 1 hour in an air atmosphere to obtain a pre-calcined material;
[0089] (2) mixing the additives and the obtained pre-sintered material, performing secondary sand grinding for 2 hours, drying to obtain a sand-ground powder with a median particle size of 1 μm, passing the sand-ground powder through an 80-mesh sieve, granulating, and molding to obtain a standard sample ring blank with a size of 12.5 mm×7.5 mm×7 mm, and then sintering to obtain the manganese-zinc ferrite material;
[0090] The additive comprises, by total mass of main components, 800 ppm of Co2O3, 500 ppm of CaCO3, 500 ppm of Nb2O5, 300 ppm of ZrO2, 300 ppm of V2O5 and 1500 ppm of TiO2;
[0091] The sintering process includes: in a balanced oxygen partial pressure atmosphere, heating to 1100°C at a rate of 1.5°C / min for a first sintering for 1 hour, then heating to 1200°C at a rate of 4°C / min for a second sintering for 0.5 hour, then cooling to 1100°C at a rate of 3.5°C / min for a third sintering for 5 hours, then cooling to 250°C at a rate of 2.5°C / min for a fourth sintering for 3 hours, and finally cooling to a termination temperature of 80°C at a rate of 0.1°C / min.
[0092] Example 4
[0093] This embodiment provides a manganese-zinc ferrite material and a preparation method thereof, which is different from Embodiment 1 in that the pre-burning temperature in step (1) is 700°C.
[0094] Example 5
[0095] This embodiment provides a manganese-zinc ferrite material and a preparation method thereof, which is different from Embodiment 1 in that the pre-burning temperature in step (1) is 900°C.
[0096] Example 6
[0097] This embodiment provides a manganese-zinc ferrite material and a preparation method thereof, which is different from Embodiment 1 in that the temperature of the second sintering in step (2) is 1090°C.
[0098] Example 7
[0099] This embodiment provides a manganese-zinc ferrite material and a preparation method thereof, which differs from Embodiment 1 in that: in step (2), the temperature of the second sintering is 1250°C.
[0100] Example 8
[0101] This embodiment provides a manganese-zinc ferrite material and a preparation method thereof, which is different from Embodiment 1 in that the fifth sintering is not performed in step (2).
[0102] Example 9
[0103] This embodiment provides a manganese-zinc ferrite material and a preparation method thereof, which is different from Embodiment 1 in that the fourth sintering is not performed in step (2), and the temperature is directly lowered to the fifth sintering temperature after the third sintering.
[0104] Comparative Example 1
[0105] This comparative example provides a manganese-zinc ferrite material and a preparation method thereof, which is different from Example 1 in that Co2O3 is not added.
[0106] Comparative Example 2
[0107] This comparative example provides a manganese-zinc ferrite material and a preparation method thereof, which is different from Example 1 in that the mass of the Co2O3 is 700ppm of the total mass of the main components.
[0108] Comparative Example 3
[0109] This comparative example provides a manganese-zinc ferrite material and a preparation method thereof, which is different from Example 1 in that the mass of the Co2O3 is 3000ppm of the total mass of the main components.
[0110] Comparative Example 4
[0111] This comparative example provides a manganese-zinc ferrite material and a preparation method thereof, which differs from Example 1 in that the Co2O3 is replaced by an equal mass of CoO.
[0112] The obtained manganese-zinc ferrite material was subjected to performance testing, and the specific method is as follows: the manganese-zinc ferrite material was placed on a SY8218 test device and its loss was tested under the conditions of 1MHz 50mT, T=25℃ / 100℃ / 120℃; and its magnetic permeability was tested at 10kHz, 0.25V, 25℃ and after being baked in an oven at 125℃ and 150℃ for 1000h. The results are shown in Table 1.
[0113] Table 1
[0114]
[0115] In summary, the anti-aging high-frequency manganese-zinc ferrite material provided by the present invention reduces the magnetostriction coefficient of the material itself through a suitable main formula ratio; reduces material loss and improves the anti-aging properties of the material through a suitable combination and addition of additives; after the ferrite material is placed in an oven and baked at 125°C and 150°C for 1000 hours, its magnetic permeability changes are less than 8% and 14%, respectively.
[0116] The present invention illustrates the detailed process equipment and process flow of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed process equipment and process flow, that is, it does not mean that the present invention must rely on the above-mentioned detailed process equipment and process flow to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A manganese-zinc ferrite material, characterized in that: The manganese-zinc ferrite material comprises a main component and an additive, wherein the main component comprises Fe2O3, ZnO and MnO; The additive includes Co2O3, and the mass of the Co2O3 is 800-2000ppm of the total mass of the main component.
2. The manganese-zinc ferrite material according to claim 1, characterized in that: Calculated as a percentage of the total amount of substances, the main components include: Fe2O3 52~56mol% ZnO 4~7mol% MnO balance.
3. The manganese-zinc ferrite material according to claim 1 or 2, characterized in that: The additive further comprises any one or a combination of at least two of CaCO3, Nb2O5, ZrO2, V2O5 or TiO2; Preferably, the mass of CaCO3 is 500 to 1000 ppm of the total mass of the main components; Preferably, the mass of Nb2O5 is 200 to 500 ppm of the total mass of the main components; Preferably, the mass of ZrO2 is 100 to 300 ppm of the total mass of the main components; Preferably, the mass of the V2O5 is 100 to 300 ppm of the total mass of the main components; Preferably, the mass of the TiO2 is 1500 to 3500 ppm of the total mass of the main components.
4. The method for preparing the manganese-zinc ferrite material according to any one of claims 1 to 3, characterized in that: The preparation method comprises the following steps: (1) mixing the main components according to the formula, performing a sand grinding and then pre-burning to obtain a pre-burned material; (2) Mixing the additives and the obtained pre-sintered material, performing secondary sand grinding and then sintering to obtain the manganese-zinc ferrite material.
5. The preparation method according to claim 4, characterized in that: The one-time sand grinding process in step (1) also includes mixing water; Preferably, the mass ratio of the main component to water is 1:(1.2-2.5); Preferably, the time of the first sanding in step (1) is 1 to 3 hours; Preferably, the pre-burning temperature in step (1) is 750-850°C; Preferably, the pre-burning time in step (1) is 1 to 3 hours; Preferably, the pre-firing atmosphere in step (1) is an air atmosphere.
6. The preparation method according to claim 4 or 5, characterized in that: The time of the secondary sand grinding in step (2) is 2 to 4 hours; Preferably, the median particle size of the powder obtained after the secondary sand grinding in step (2) is 0.8 to 1.2 μm.
7. The preparation method according to any one of claims 4 to 6, characterized in that: The second sand grinding in step (2) further includes screening, granulation and molding; Preferably, the mesh size of the sieve is 30 to 80 meshes; Preferably, a granulating agent is added during the granulation process; Preferably, the granulating agent comprises PVA and / or PVB; Preferably, the mass of the granulating agent is 8-15wt% of the mass of the powder after secondary sand grinding.
8. The preparation method according to any one of claims 4 to 7, characterized in that: The sintering in step (2) is carried out under a balanced oxygen partial pressure atmosphere; Preferably, the sintering in step (2) includes a first sintering, a second sintering, a third sintering, and a fourth sintering; Preferably, the first sintering temperature is 1000-1100°C; Preferably, the first sintering holding time is 0.5 to 1 h; Preferably, the heating rate of the first sintering is 1-3°C / min; Preferably, the second sintering temperature is 1100-1200°C; Preferably, the second sintering holding time is 0.1 to 0.5 h; Preferably, the heating rate of the second sintering is 3-5°C / min; Preferably, the temperature of the third sintering is 1000-1100° C.; Preferably, the holding time of the third sintering is 3 to 5 hours; Preferably, the cooling rate of the third sintering is 3-5°C / min; Preferably, the temperature of the fourth sintering is 250-300°C; Preferably, the fourth sintering holding time is 3 to 5 hours; Preferably, the cooling rate of the fourth sintering is 2.5-5°C / min; Preferably, after the fourth sintering is completed, the temperature is lowered to the termination temperature; Preferably, the termination temperature is 40 to 80°C; Preferably, the cooling rate to the termination temperature is 0.1-0.5°C / min.
9. The preparation method according to any one of claims 4 to 8, characterized in that: The preparation method comprises: (1) mixing the main components according to the formula amount, mixing the main components with water at a mass ratio of 1: (1.2-2.5), sand-milling for 1-3 hours, drying, and then pre-calcining at a temperature of 750-850° C. for 1-3 hours in an air atmosphere to obtain a pre-calcined material; (2) mixing the additive and the obtained pre-sintered material, performing secondary sand milling for 2 to 4 hours, drying to obtain a sand milled powder with a median particle size of 0.8 to 1.2 μm, passing the sand milled powder through a 30 to 80 mesh sieve, granulating, molding and sintering to obtain the manganese zinc ferrite material; The sintering process includes: in a balanced oxygen partial pressure atmosphere, heating to 1000-1100°C at a rate of 1-3°C / min for a first sintering for 0.5-1h, then heating to 1100-1200°C at a rate of 3-5°C / min for a second sintering for 0.1-0.5h, then cooling to 1000-1100°C at a rate of 3-5°C / min for a third sintering for 3-5h, then cooling to 250-300°C at a rate of 2.5-5°C / min for a fourth sintering for 3-5h, and finally cooling to a termination temperature of 40-80°C at a rate of 0.1-0.5°C / min.
10. An application of the manganese-zinc ferrite material according to any one of claims 1 to 3, characterized in that: The manganese-zinc ferrite material is used for power electronic components.
Citation Information
Patent Citations
Preparation method of manganese-zinc soft magnetic ferrite material with ultra-low-temperature magnetic permeability stability
CN110183221A